Professor Sir Leon Radzinowicz, LL.D., FBA - Hood, Roger (The British journal of criminology, 1997)
Pays tribute to criminologist Sir Leon Radzinowicz of Great Britain. Contributions in the field of criminology; Educational background; Radzinowicz's belief that there must be a link between criminology and criminal policy; List of achievements attained by Radzinowiczin the field